Uma viagem sociolinguística pelas veredas do sistema de pronomes possessivos no português falado em Luanda-Angola - Trindade, Marinez Aparecida Almeida da Silva (2021)
This work described and analyzed the variable use of indicative expressions of possession referring to all grammatical persons in the language spoken in Luanda, based on the analysis of the investigation of synthetic and analytical forms, according to the respective examples:“a língua materna que seus pais têm pra poder também comunicar-se com seus pais, é [...]” (INF.: I. L., W2MCL) and “Mas não vive dentro da minha casa, vive nos lares deles. (Inf.: P. J., HMCL). A representative sample of Angolan Portuguese (PA) was investigated, extracted from the project collection In search of the roots of Brazilian Portuguese – Phase III: Morphosyntactic Studies, based at NELP - Center for Studies in Portuguese Language at the State University of Feira de Santana (UEFS). The research considered 34 interviews with participants that were distributed by level of education, sex, place of origin and native language, in an attempt to identify convergences or divergences of linguistic changes in the variety of Portuguese as an official language compared to Brazilian Portuguese - PB, using as a theoretical framework: Araújo (2005, 2010), Silva (1996), Petter (2007), Neves (2000), and more. Research was also considered from a socio-historical point of view (ALENCASTRO, 2000; ANDRADE, 1997; DIAS, 1991; ZAU, 2011, and more), assuming that the current characteristics of Luandan language result from changes induced by the contact of Portuguese with African languages. The analyzed material was composed by 1,380 data, divided in the three possessive pronouns, trying to verify whether the linguistic behavior of the speakers that compose the corpus has a conservative basis or it is in a process of change with regard to the grammatical phenomenon studied. The results showed that the variation / change process is incipient in the PA, being the preferred use for the canonical forms, that is, possessive pronouns in the synthetic form, in contrast to what occurs in the BP - variety in which the conservative form is undergoing restructuring. The only variation identified in the PA refers to the third person (seu~dele) which was interpreted by a structural motivation, meaning that it is motivated by the system itself, being in line with the grammatical norm. The study of the subject in question has not been finished, which provides and suggests future investigations that will continue the analysis regarding the study strategies on the subject in question and the basis for further research in relation to the Portuguese variety of Angola and / or varieties of Portuguese language in other African countries.